A ruthenium cis-dihydride with 2-phosphinophosphinine ligands catalyses the acceptorless dehydrogenation of benzyl alcohol. Issue 38 (3rd September 2021) - Trodden, Elizabeth C.; Delve, Matthew P.; Luz, Christian; Newland, Robert J.; Andresen, John M.; Mansell, Stephen M.
Abstract : The first ruthenium dihydride stabilised with phosphinine ligands is described. Formed in situ, it was shown to catalyse the acceptorless dehydrogenation (AD) of benzyl alcohol to benzyl benzoate. Abstract : The first ruthenium dihydride complex featuring a phosphinine ligand cis -[Ru(H)2 (2-PPh2 -3-Me-6-SiMe3 -PC5 H2 )2 ] was synthesised exclusively as the cis -isomer. When formed in situ from the reaction of cis -[Ru(Cl)2 (2-PPh2 -3-Me-6-SiMe3 -PC5 H2 )2 ] with two equivalents of Na[BHEt3 ], as demonstrated by 31 P and 1 H NMR spectroscopy, the catalysed acceptorless dehydrogenation of benzyl alcohol was observed leading to benzyl benzoate in up to 70% yield.